2022
DOI: 10.1108/ijshe-09-2021-0392
|View full text |Cite
|
Sign up to set email alerts
|

Teaching sustainability: does style matter?

Abstract: Purpose This paper aims to analyze how a tangram activity improved students’ abilities to explain sustainability, articulate a positive perception of sustainable design and relate sustainability with innovation in engineering design. Design/methodology/approach The concept of paradigm shift was introduced in the classroom by using a tangram activity to help students understand that sustainable design requires out-of-the-box thinking. Instructors from three institutions teaching various levels of sustainabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Given the sudden switch to online or blended teaching during the pandemic, further debate over the “learner-centred and action-oriented” approach will be essential if the current undergraduates are to become the “change agents” that inspire SDG implementation (Fokdal et al , 2019). Ozis et al (2022) contend that to reposition the conventional paradigm required for sustainable design, HEI instructors should use straightforward, approachable active learning methodologies in the classroom and across the curriculum. One inspirational environmental education tool to be investigated further is game-based learning, either via in-person board games or online role-player workshops (Chen and Ho, 2022).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Given the sudden switch to online or blended teaching during the pandemic, further debate over the “learner-centred and action-oriented” approach will be essential if the current undergraduates are to become the “change agents” that inspire SDG implementation (Fokdal et al , 2019). Ozis et al (2022) contend that to reposition the conventional paradigm required for sustainable design, HEI instructors should use straightforward, approachable active learning methodologies in the classroom and across the curriculum. One inspirational environmental education tool to be investigated further is game-based learning, either via in-person board games or online role-player workshops (Chen and Ho, 2022).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Wang et al [20] found that case study and interdisciplinary team teaching have a positive impact on students' thinking and perceptions of sustainable development when studying the impact of curriculum pedagogy on sustainability. Some researchers, such as Martínez Casanovas et al [21] and Ozis et al [22], proposed that participatory methods include problem-based and experiential learning, e.g., by adopting active teaching methods in class, students engage in the learning process and avoid passive acceptance of knowledge, which is conducive to improving students' abilities to solve problems and so on [23]. Lozano et al [24] explored the relationship between teaching and sustainable development competences.…”
Section: Influence Of Teachingmentioning
confidence: 99%
“…One promising avenue for HEIs to promote innovation and develop teamwork skills amongst college students in a healthy way, also allowing the achievement of SDGs, is to incorporate active learning methodologies (e.g., problem-based learning, gamification, game-based learning (GBL), flipped learning, learning by doing, service-learning (S-L), etc.) [44][45][46][47]. For instance, Martínez-Casanovas et al [46] showed, in their recent study, that problem-based learning and case studies, such as active learning methodologies, promoted and enhanced SDGs.…”
Section: Innovation Behaviors In Hementioning
confidence: 99%
“…Active learning methodologies place college students at the center of the teachinglearning processes, providing them opportunities for personal discovery, which improves the learning process [44], as well as for the development of their skills [48], such as creative thinking, problem solving, communication, teamwork and innovative performance [49]. In the last few decades, a growing body of research has shown the potential of these methodologies, such as GBL, to develop and foster amongst college students' engagement, intrinsic motivation, academic performance, interaction, socialization, students' confidence for teamwork and team building, creativity and innovation [50][51][52][53][54][55][56][57].…”
Section: Innovation Behaviors In Hementioning
confidence: 99%